Rationality in the Use of Packaging: A Reflection on the Food Sector - Neger, Cristina Loyola (2023)
The text highlights the historical importance of packaging in transporting products, driving economic development, and creating business opportunities. However, the current sustainability challenge stands out, with non-sustainable packaging contributing to pollution and waste. The transition to sustainable packaging may generate additional costs but strengthens the brand and attracts consumers concerned about environmental issues. The current context, marked by attention to ESG, encourages the industry to develop more innovative and sustainable packaging. Consumer awareness of the importance of sustainability puts pressure on companies to adopt more responsible practices. Flexible packaging is highlighted as a viable alternative that reduces the use of plastic and its environmental impact. The text emphasizes the need to rethink production and consumption practices, aiming at environmental preservation and the circular economy.